Research on the Composition and Dance Form of the "Tang Gong Ye Yan" Dance - Guo, Yihan; Chansuwan, Pattamawadee (Journal of Posthumanism, 2025)
In recent years, the traditional Chinese dance performance of “Tang Gong Ye Yan” has gained widespread attention for its outstanding choreography and cultural richness. This paper explores the structural composition and dance forms within ’Tang Gong Ye Yan ’ by analyzing its unique elements and performance techniques. Using a combination of visual analysis, historical literature review, and field interviews with dance professionals, this study investigates the dance’s historical context, aesthetic principles, and choreography techniques. Through these methodologies, the paper delineates how the intricate structure and the employment of traditional dance forms contribute to the revitalization and popularization of Tang Dynasty culture. The study’s findings reveal the intricate balance between historical authenticity and artistic innovation within the performance and how these elements engage contemporary audiences. Ultimately, the research offers an in-depth understanding of the "Tang Gong Ye Yan" Dance, providing valuable insights for scholars and practitioners in traditional Chinese dance.